Pertumbuhan dan Produksi Tanaman Sawi Pakcoy (Brassica rapa L.) yang Dibudidayakan pada Berbagai Komposisi Media Tanam dan Konsentrasi Pupuk Organik Cair dengan Sistem Vertikultur - Efendy, Yessy Pristika; Suhardjono, Hadi; Widiwurjani, Widiwurjani (Universitas Lampung, 2024)
Pakcoy (Brassica rapa L.) is one of the important and popular vegetable crops in Indonesia. City development and massive urbanization have resulted in the shrinking of agricultural land in urban areas. Home gardens have great potential if managed optimally and planned. Therefore, the concept of urban farming with the vertical farming method can be a solution. This study aimed to determine the optimal composition of planting media and liquid organic fertilizer (LOF) concentration for the growth and production of pakcoy plants. This study used a completely randomized design (CRD) with two factors. The first factor was the composition of the planting medium, which consisted of three levels: soil, compost, and goat manure with a ratio of 1:1:1, 1:1:2, and 1:2:1. The second factor was the concentration of LOF and urea, which consisted of four levels: 1 gram urea, 2 ml/liter water, 4 ml/liter water, and 6 ml/liter water. The results of the study showed that the combination of planting medium composition and LOF concentration had an effect on all observation parameters. The combination of planting medium composition 1:1:2 and LOF concentration of 4 ml/liter water produced the best results for all observation parameters, namely plant height, number of leaves, total fresh weight, fresh head weight, fresh root weight, and plant dry weight. Key words : Pakcoy mustard, verticulture, media composition, concentration, LOF